Toward A Sustainable and Inclusive Consolidation in Lithuania : Past Experience and What is Needed Going Forward - Geng, Nan. (Washington, D.C. : International Monetary Fund, 2013)
This paper reviews Lithuania's fiscal consolidation since 2009, assesses the contribution of revenue and expenditure to the consolidation, evaluates the quality of measures, and draws lessons for the future. It finds that, despite having the lowest revenue-to-GDP ratio in the EU, Lithuania's fiscal adjustment has so far relied mainly on expenditure measures, with the quality of measures deteriorating over time. The analysis also suggests that Lithuania's tax system, in comparison with other EU countries and regional peers, is skewed toward labor and consumption taxes, and plays a more limited role in income redistribution, especially in the upper income brackets. The paper argues therefore that there is ample scope to implement high quality revenue measures in order to complete the fiscal adjustment in the medium term in a sustainable and inclusive manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet